Alien plant invasion on the Agulhas Plain : a detailed description of invasion patterns - Blanchard, Ryan (Department of Biological Sciences, 2017)
Invasive alien species occur within several biodiverse regions of South Africa. It is not yet fully understood the extent to which invasive alien species affect natural vegetation. It is important to classify such species based on abundance and distribution in order to determine invasion patterns and set priorities for management within a region. Such a study was adapted for the Agulhas Plain of South Africa in the Cape Floristic Region. Eucalyptus lehmannii was recognised as the top invasive alien species, occupying both natural and transformed landscapes at high densities, >130% canopy cover. Acacia saligna and Acacia cyclops are the most widely distributed species, covering 41 % and 53% of the total area. Effectively determining invasive alien species richness required the use different variables to those used in this study. Invasive alien species invasion pattern was classified into two groups, namely coastal invasion and interior invasion. These characteristics differed with regards to vegetation types and species composition. Natural vegetation within the Mountain fynbos (100% invaded), Dune fynbos (91 % invaded) and Mountain top fynbos (99% invaded) vegetation types were largely threatened by invasive alien species. Vegetation types largely affected by transformation include Elim asteraceous fynbos (89% transformed) and Renoster fynbos. The invasion patterns described could be used in prioritisation of manageable land.